Analisis Angka Kesembuhan Dan Pengobatan Lengkap Serta Keberhasilan Pengobatan Tuberkulosis Di kabupaten Aceh Besar 2023 - Nurdin, Ambia; diana; khairuman; rahayu, dian (Public Health Journal, 2024)
Abstract Tuberculosis (TB) is an infectious disease that is still a health problem in Indonesia, including in Aceh Besar. This study aims to analyze the cure and complete treatment rates and the success of TB treatment by gender and district in Aceh Besar in 2023.Data were taken from the Aceh Besar Health Profile in 2023. Data were analyzed using descriptive statistics.The results showed that the number of bacteriologically confirmed pulmonary TB cases found and treated in Aceh Besar in 2023 was 335 cases, with 238 male cases and 97 female cases. The total number of TB cases found and treated was 439, with 300 male and 139 female cases. The bacteriologically confirmed pulmonary TB cure rate was 46.2%, with a male cure rate of 44.2% and a female cure rate of 48.5%. The complete treatment rate for all TB cases was 52.3%, with a male complete treatment rate of 51.7% and a female complete treatment rate of 53.1%. The treatment success rate for all TB cases was 87.1%, with a male treatment success rate of 85.8% and a female treatment success rate of 88.4%. Based on the results of the study, the cure and complete TB treatment rates in Aceh Besar are still below WHO standards. This suggests that more work needs to be done to improve TB treatment success in this area.